THE DIFFERENCES IN BODY COMPOSITION BETWEEN FOOTBALL PLAYERS OF DIFFERENT RANK COMPETITIONS - Stevo Popović; Miroslav Smajić; Aleksandar Joksimović; Bojan Mašanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
This research was aimed at gaining relevant knowledge about important differences with respect to body composition of the football players of different rank competitions. The sample included 425 respondents, divided into three subsample groups. The first subsample group was comprised of 368 respondents who were attending EUROS 2008; the second subsample group was comprised of 26 respondents who practice football at a Football Club "Vojvodina" from Novi Sad, while the third subsample included 31 respondents who play football only recreationally. The sample of variables contained: ages, body height, body mass, Ideal Body Mass and Body Mass Index. The results of the measuring were analyzed by multivariate analysis (MANOVA) and univariate analysis (ANOVA). Based on the results it was concluded that significant differences occur in multivariate level, as well as between next variables: ages, body mass and Body Mass Index at a significance level of p=.05.